1997
DOI: 10.1038/sj.gt.3300490
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antibody response to human tumor antigens by gene therapy using a fusigenic viral liposome vaccine

Abstract: Development of effective cancer vaccines would help pre-MAGE-1 and -3 IgG antibody responses, respectively. Anivent and control tumor progression. A novel approach of mals immunized with plasmid alone did not induce antiimmunizing against tumor antigens is in vivo gene vacci-MAGE-1 or -3 IgG responses. Antibody responses could nation. We have developed a fusigenic viral liposome vecbe enhanced on reimmunization with the gene vaccines. tor using HVJ (hemagglutinating virus of Japan) and lipoMuscle biopsies take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Previously, we have shown that anti-MAGE-A3 Ab will cross-react with MAGE-A1 protein. 10 Therefore, if the melanoma lesion expresses a MAGE-A protein with significant homology to MAGE-A1, it has a significant potential to produce a crossreacting immune response.…”
Section: Fujii Huang Fong Et Al: Intratumoral Ifn-␥ Retroviral Delmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that anti-MAGE-A3 Ab will cross-react with MAGE-A1 protein. 10 Therefore, if the melanoma lesion expresses a MAGE-A protein with significant homology to MAGE-A1, it has a significant potential to produce a crossreacting immune response.…”
Section: Fujii Huang Fong Et Al: Intratumoral Ifn-␥ Retroviral Delmentioning
confidence: 99%
“…These modalities include delivery to tumor cells, vaccination with tumorassociated antigen(s) (Ags), and delivery of specific cytokine(s) for immunomodulation or modulation of tumor cell growth and properties. [7][8][9][10][11] The delivery of cytostatic cytokines such as interferon-␥ (IFN-␥) has shown promising results in animal and human studies. IFN-␥ is a type II IFN, whereas IFN-␣ and IFN-␤ are type I.…”
mentioning
confidence: 99%
“…11 Recently, we demonstrated that repetitive gene transfer can be achieved by HVJ-liposome vector system without side-effects or neutralization of the delivery system. 12 In our previous studies we demonstrated that when pcDNA3 plasmid containing the human tumor antigen genes MAGE-1 and MAGE-3 were encapsulated in HVJ-liposomes and injected into mice intramuscularly, there were no side-effects and there was highly efficient transfection of muscle cells for several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…12 In our previous studies we demonstrated that when pcDNA3 plasmid containing the human tumor antigen genes MAGE-1 and MAGE-3 were encapsulated in HVJ-liposomes and injected into mice intramuscularly, there were no side-effects and there was highly efficient transfection of muscle cells for several weeks. 11 Recently, we improved the HVJ-liposome system for more efficient gene delivery by changing the lipid components of the liposomes, and developed a novel HVJ-AVE (artificial viral envelope) liposome which increased gene expression in mouse skeletal muscle and liver five to 10 times higher compared with conventional HVJliposomes. 13 In this study, we assessed the fusigenic HVJ-liposome system to transfer the gene encoding human gp100 antigen into mice intramuscularly.…”
Section: Introductionmentioning
confidence: 99%
“…The hemagglutinating virus of Japan ( HVJ ) -liposome gene transfer method enables delivery of nucleic acids or proteins directly and efficiently into host cells in vivo by means of the virus' cell fusion machinery. 19 We have developed many types of liposomes with the HVJ envelope and found that HVJ anionic liposomes were effective for transfer of genes to solid organs such as liver and muscle, whereas HVJ cationic liposomes were preferable for gene transfer to surface areas of organs such as bronchial epithelium and biliary epithelium. 20 -22 Cationic liposomes appeared to be more effective for cancer gene therapy than the anionic type.…”
mentioning
confidence: 99%